Investigation of Extended Bandwidth Hearing Aid Amplification on Speech Intelligibility and Sound Quality in Adults with Mild-to-Moderate Hearing Loss. - Seeto, Angeline; Searchfield, Grant D. (Journal of the American Academy of Audiology, 2018)
Background: Advances in digital signal processing have made it possible to provide a wide-band frequency response with smooth, precise spectral shaping. Several manufacturers have introduced hearing aids that are claimed to provide gain for frequencies up to 10-12 kHz. However, there is currently limited evidence and very few independent studies evaluating the performance of the extended bandwidth hearing aids that have recently become available. Purpose: This study investigated an extended bandwidth hearing aid using measures of speech intelligibility and sound quality to find out whether there was a significant benefit of extended bandwidth amplification over standard amplification. Research Design: Repeated measures study designed to examine the efficacy of extended bandwidth amplification compared to standard bandwidth amplification. Study Sample: Sixteen adult participants with mild-to-moderate sensorineural hearing loss. Intervention: Participants were bilaterally fit with a pair of Widex Mind 440 behind-the-ear hearing aids programmed with a standard bandwidth fitting and an extended bandwidth fitting; the latter provided gain up to 10 kHz. Data Collection and Analysis: For each fitting, and an unaided condition, participants completed two speech measures of aided benefit, the Quick Speech-in-Noise test (QuickSIN™) and the Phonak Phoneme Perception Test (PPT; high-frequency perception in quiet), and a measure of sound quality rating. Results: There were no significant differences found between unaided and aided conditions for QuickSIN™ scores. For the PPT, there were statistically significantly lower (improved) detection thresholds at high frequencies (6 and 9 kHz) with the extended bandwidth fitting. Although not statistically significant, participants were able to distinguish between 6 and 9 kHz 50% better with extended bandwidth. No significant difference was found in ability to recognize phonemes in quiet between the unaided and aided conditions when phonemes only contained frequency content,6 kHz. However significant benefit was found with the extended bandwidth fitting for recognition of 9-kHz phonemes. No significant difference in sound quality preference was found between the standard bandwidth and extended bandwidth fittings. Conclusions: This study demonstrated that a pair of currently available extended bandwidth hearing aids was technically capable of delivering high-frequency amplification that was both audible and useable to listeners with mild-to-moderate hearing loss. This amplification was of acceptable sound quality. Further research, particularly field trials, is required to ascertain the real-world benefit of high-frequency amplification.